2012
DOI: 10.4103/1742-6413.94570
|View full text |Cite
|
Sign up to set email alerts
|

Dual color multiplex TTF-1 + Napsin A and p63 + CK5 immunostaining for subcategorizing of poorly differentiated pulmonary non-small carcinomas into adenocarcinoma and squamous cell carcinoma in fine needle aspiration specimens

Abstract: Background:The distinction of lung adenocarcinoma (ADC) from squamous cell carcinoma (SCC) has important therapeutic implications. Napsin A is a recently developed marker, which has shown high specificity for lung tissue in the surgical pathology specimens. In this study, we have evaluated whether the use of a panel of novel multiplex cocktails of TTF-1 + Napsin A and p63 + CK5 for dual color immunostaining will improve the diagnostic accuracy of lung adenocarcinoma and squamous cell carcinoma in fine needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Several recent studies have proposed to combine individual markers as a dual or triple marker for subtyping NSCLC; and showed variable sensitivities and specificities [25], [26], [27] and [28]. Fatima et al have studied the combination of TTF1 and Napsin A in diagnosing lung ADC using FNA cell block material, and they showed a sensitivity and specificity of 74% and 87%, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have proposed to combine individual markers as a dual or triple marker for subtyping NSCLC; and showed variable sensitivities and specificities [25], [26], [27] and [28]. Fatima et al have studied the combination of TTF1 and Napsin A in diagnosing lung ADC using FNA cell block material, and they showed a sensitivity and specificity of 74% and 87%, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although Brown’s study demonstrated an optimal performance of the desmoglein 3 plus CK5 in subtyping SqCC, a recent study by Sakai et al showed that desmoglein 3 was also variably expressed by a subset of lung ADCs [30]. Sethi et al have reported that the combination of TTF1 and Napsin A had 100% sensitivity and specificity in ADC, and the combination of p63 and CK5 had 100% sensitivity and specificity in SqCC [27]. Even though a few studies suggested 100% sensitivity and 100% specificity of certain markers, sampling error and bias should be considered when interpreting the data, particularly when studies were performed using a small set of selected samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, although no published prior knowledge was used for the identification of this gene, KRT5 is a well-known marker used to distinguish between AC and SCC. 18 It has also been identified in a number of the published signatures and by the team with the third best performance in the sbv IMPROVER LC Challenge. 19 The empirical method used in the challenge included visual inspection of the profiles of a set of candidates in the test set: profiles were identified according to their ability to separate samples in two clusters (assuming these two clusters would be AC and SCC samples).…”
Section: Discussionmentioning
confidence: 97%